Using the Theory of Planned Behavior to explore hospital-based nurses’ intention to use peripherally inserted central catheter (PICC): a survey study - Bertani, Laura; Carone, Maria; Caricati, Luca; Demaria, Serena; Fantuzzi, Silvia; Guarasci, Alessandro; Pirazzoli, Luca (Acta Biomedica Atenei Parmensis, 2016)
Background and aim of the work: The peripherally inserted central catheters (PICC) have become an alternative to the traditional CVC. PICCs are usually inserted by trained nurses who decided to attend and complete a special training on PICC insertion and management. The present work aimed to investigate the intention of using PICC in a sample of hospital-based nurses using the theory of planned behavior as theoretical framework. Methods: A cross-sectional design was used in which a questionnaire was delivered to 199 nurses. Results: According to the theory of planned behavior, the attitude toward the use of PICC, subjective norms and perceived self-efficacy predicted the intention to use PICC. Contrary to the expectations, the effect of subjective norms on intention to use PICC was mediated by attitude and self-efficacy. Finally, age of participants was negatively related to the intention to use the PICC. Conclusions: The theory of planned behavior offers a useful framework to explain nurses’ intention to use PICC. Shared norms favoring the use of PICC seem to increase both nurse’s positive attitudes and self-efficacy whit respect to the use of these devices. Thus, it appears that to train professionals individually does not necessarily results in an increased use of PICC.